A contribution to the knowledge of the centipedes of Saint Barthélemy Island (French Antilles), with re-descriptions of Newportia heteropoda Chamberlin, 1918 and Cormocephalus impressus Porat, 1876 (Chilopoda: Scolopendromorpha) - Schileyko, Arkady A. (Zootaxa, 2018)
The paper provides descriptions of three scolopendromorph centipede species collected in Saint Barthélemy Island. Two of them, Newportia heteropoda Chamberlin, 1918 and Cormocephalus impressus Porat, 1876 are redescribed and their systematic position is discussed. The taxonomic status of Newportia cubana Chamberlin, 1915 is revised, this nominal taxon being treated as the subspecies N. longitarsis cubana stat. nov. C. guildingii Newport, 1845 is confirmed as a valid species of which C. bonaerius Attems, 1928 is considered as a junior synonym. An identification key to the Scolopendromorpha of the island is presented.